2015
DOI: 10.1186/s12885-015-1592-3
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 regulated epithelial-mesenchymal transition and migration/invasion enhancement in non-small cell lung cancer

Abstract: BackgroundYKL-40 is a secreted inflammatory protein that its overexpression has been reported to correlate with poor outcome of various malignant diseases, especially in cancer. However, the function of this protein is still unclear.MethodsThe clinical prognosis of non-small cell lung cancers (NSCLC) patients and their clinical YKL-40 expressions were obtained from the Prognoscan database. The expressions of YKL-40 in patient samples were determined by Western Blotting assay. YKL-40 gene knockdown and overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 26 publications
1
37
1
Order By: Relevance
“…Additionally, Shao et al [25], have identified that the YKL-40 expression levels are associated with breast cancer vascular invasion. Jefri et al [27], assessed YKL-40 gene expression in lung cancer and found similar association between gene expression and patients' prognosis of lung cancer.…”
Section: E M Fouad Et Al Advances In Breast Cancer Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, Shao et al [25], have identified that the YKL-40 expression levels are associated with breast cancer vascular invasion. Jefri et al [27], assessed YKL-40 gene expression in lung cancer and found similar association between gene expression and patients' prognosis of lung cancer.…”
Section: E M Fouad Et Al Advances In Breast Cancer Researchmentioning
confidence: 88%
“…Hence, YKL-40 could to be used as a novel prognostic factor for expecting out come of carcinoma patients, more over it could be a promising targeted therapy [34]. Jefri et al [27] & Hao et al [28], proved the role of YKL-40 in EMT induc- kinase (PI3K)/AKT/mTOR cascade, which is connected with tumor survival, invasion, and metastasis and is a central feature of EMT [28].…”
Section: E M Fouad Et Al Advances In Breast Cancer Researchmentioning
confidence: 99%
“…21 YKL-40 overexpression might also be associated with non-small cell lung cancer CL1-1, CL1-5 cells (NSCLC). 24 Studies have explored the inhibitory effects of YKL-40 on tumor growth and angiogenesis induced by YKL-40 in vivo. In astrocytoma, YKL-40 has been shown to induce angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In YKL-40 overexpressed cell line, the expression of E-cadherin, a marker of epithelial cells, was significantly lower; and the expression of markers of mesenchymal cells (N-cadherin, Vimentin) was significantly higher as well as other EMT regulators (Snail, Slug, and Twist) [35]. Moreover, inhibition of YKL-40 reduced the tube formation in vitro and suppressed tumor growth, angiogenesis, and progression of brain tumors [28].…”
Section: The Role Of Clps In Angiogenesis and Chemotaxismentioning
confidence: 96%